BIOCHEMICAL PARAMETERS OF THE INTENSITY OF SYSTEMIC INFLAMMATORY RESPONSE IN THE ASSESSMENT OF BIOCOMPATIBILITY OF POLYCAPROLACTONE/VATERITE SCAFFOLDS - E. A. Galashina; Yu. A. Chibrikova; A. N. Ivanov; E. V. Gladkova; I. A. Norkin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
In this study, we analyzed biocompatibility of polycaprolactone/vaterite scaffolds by assessing the dynamics of systemic inflammatory response. We detected an increase in the CRP level after 7 days and no changes in the level TNF-α and IL-1β after 7 and 21 days, which indicates a weak and short-term inflammatory reaction and is a pathogenetic component of matrix biocompatibility.